Financing higher education in Africa. (Directions in development (Washington, D.C.). Human development., 2010)
Sustainable growth in SSA is contingent on the capacity of States to diversify their economies and thus train human capital that will help carry out and support this transformation. Higher education plays a key role in training qualified individuals who will be able to implement new technologies, and use innovative methods to establish cost-efficient and effective enterprises and institutions. Through research and increased knowledge, higher education can also help address the challenges arising from the increase in the size of the population, limited arable land, endemic diseases, urbanizatio.